Nutritional Profile of Awyu and Yaqai Girls in Mappi Regency, South Papua: Marice Dou, Postgraduate Program, Biology Study Program, University of Papua - Marice Dou; Febriza Dwiranti; Elda Irma Jeanne Joice Kawulur (Jurnal Natural, 2026)
ABSTRACT Nutritional status is a condition determined by the extent to which the body’s physiological needs for energy and nutrients are met through dietary intake. Primary school age is a critical period for physical growth, cognitive development, and the maturation of organ systems. Nutritional imbalance during this stage may have long-term consequences, including stunting, reduced immune function, and impaired brain development. The aim of this study was to examine the body growth patterns of Awyu and Yaqai girls. This study used a cross-sectional design. Physical growth status was assessed in 163 girls aged 6–12 years at the primary school level, consisting of 84 Awyu girls and 79 Yaqai girls in Mappi Regency, South Papua Province. Nutritional status was determined using the body mass index-for-age (BMI-for-age) index based on anthropometric measurements, including height (cm) and weight (kg), as well as interviews. The results showed that the nutritional profiles of girls from both ethnic groups were not substantially different. Most of the children had a good nutritional status, with 98 children (98.15%) classified as normal, 2 children (1.22%) were classified as overweight, and none were classified as thinness and obese. Keyword : Mappi, girl, cross-sectional, nutritional status